Microsoft 365 PowerPoint - Lowe, Doug, 1959- (--For dummies., 2025)
"Present like a pro, with the top-selling PowerPoint book on the market Since 1999, PowerPoint For Dummies has been giving readers a jargon-free way to compose compelling presentations. This update covers the latest release of Office and Office 365. Learn the basics of creating a slide deck in PowerPoint, then discover the dynamic features you can use to give your slides a bit of pizazz. Import data from other applications, collaborate in the cloud, and incorporate charts, graphics, and videos into your presentations. Plus, learn how to use Microsoft's new Copilot AI tool-integrated right into the application. Consider this book your first step to making a splash with PowerPoint! Create your first PowerPoint slide deck and add presentation notes Improve the design of your slides with templates and best-practice tips Add animations, change your font style, and insert images and drawings Share your presentation with audiences in a virtual setting New and not-so-new PowerPoint users who need a guide to the basics of building a successful presentation will love this up-to-date, beginner-friendly book." -- ONIX annotation.